TINJAUAN YURIDIS PENGUJIAN FORMIL UNDANG-UNDANG DI MAHKAMAH KONSTITUSI - fudika, moza dela (UIR Law Review, 2022)
One of the powers of the Constitutional Court is to carry out legal review of the 1945 Constitution. This review consists of formal review and material review. In implementing the authority for formal review, not a single request for formal review has been granted by the Constitutional Court. One of the problems, if viewed from a normative perspective, is that the touchstone for the implementation of judicial review is the law, not the 1945 Constitution as intended in the provisions of Article 24C paragraph (1) of the 1945 Constitution.